Cardiotoxin III Inhibits Proliferation and Migration of Oral Cancer Cells through MAPK and MMP Signaling. (8th April 2013) - Yen, Ching-Yu; Liang, Shih-Shin; Han, Lo-Yi; Chou, Han-Lin; Chou, Chon-Kit; Lin, Shinne-Ren; Chiu, Chien-Chih
Abstract : Cardiotoxin III (CTXIII), isolated from the snake venom of Formosan cobra Naja naja atra, has previously been found to induce apoptosis in many types of cancer. Early metastasis is typical for the progression of oral cancer. To modulate the cell migration behavior of oral cancer is one of the oral cancer therapies. In this study, the possible modulating effect of CTXIII on oral cancer migration is addressed. In the example of oral squamous carcinoma Ca9-22 cells, the cell viability was decreased by CTXIII treatment in a dose-responsive manner. In wound-healing assay, the cell migration of Ca9-22 cells was attenuated by CTXIII in a dose- and time-responsive manner. After CTXIII treatment, the MMP-2 and MMP-9 protein expressions were downregulated, and the phosphorylation of JNK and p38-MAPK was increased independent of ERK phosphorylation. In conclusion, CTXIII has antiproliferative and -migrating effects on oral cancer cells involving the p38-MAPK and MMP-2/-9 pathways.